(untitled) (Bangladesh Journal of Medicine, 2013)
Objective: The key to blood Pressure (BP) control is good BP measurement. If BP measurements are not done accurately and reliably, there is a potential for great harm and great cost. Measuring blood pressure is a routine procedure but errors are frequently committed during recording. The aim of the study was to look at the prevalent practices in the institute regarding BP recording. Methods and Materials: This study was conducted in the department of Medicine, Surgery and Gynaecology and Obstetrics in Enam Medical College, Savar. This is an prospective observational study performed amongst 50 doctors in EMCH. Doctors in each three departments were observed by one observer in each department during the act of BP recording. The observer was well versed with the guidelines issued by British Hypertension Society (BHS) and the deviations from the standard set of guidelines were noted. The errors were defined as deviations from these guidelines. The results were recorded as percentage of doctors committing these errors and analysis of results was done manually with percentage and number. Results: In our study, 100% doctors used aneroid type sphygmomanometer. Ninety percent of apparatus were without error. Ninety six percent of the BP cuff was of standard size. Twenty two percent of the doctors did not let the patient rest before recording BP. None of them recorded BP in both arms. In outpatient setting, 70% recorded blood pressure in sitting position and 30% in supine position. In 44% patients where BP was recorded in sitting position BP apparatus was below the level of heart and 60% did not have their arm supported. Eighty four percent did not use palpatory method before checking the BP by auscultation. Sixty percent lowered the BP at a rate of more than 2 mm/s. Seventy six percent recorded BP only once and 75 % of the rest reinflated the cuff without completely deflating and allowing rest before a second reading was obtained. Conclusion: Although the assessment of BP is the most cost-effective procedure in medicine, it is rarely performed according to guidelines. Efforts should be taken to improve the practice of BP measurement which would have a major impact on the health of the population. DOI: http://dx.doi.org/10.3329/bjmed.v22i1.13594 Bangladesh J Medicine 2011; 22: 12-16